I documenti d'archivio per la storia della biblioteca del Real Museo Mineralogico - de Pascale, Giovanna (Cavoliniana. Monografie della Società dei Naturalisti in Napoli, 2023)
The Royal Mineralogical Museum of the University of Naples Federico II can be a MAB in essence, a place where archive, library and museum coexist; for decades it was led by an illustrious mineralogist, Professor Arcangelo Scacchi, geologist and volcanologist, who also assumed the position of Rector of the University for several terms.Through the documents drawn up by the director and the correspondence held with exponents of the academic and institutional world and carefully preserved, it is possible to reconstruct not only the more than two hundred year history of the museum, but also its rich bibliographic heritage. Above all, of this, of the interweaving of purchases of minerals and books, of the studies for conservation and the idea of​​forming a "specialized" library for the use of mineralogists and of the conspicuous documentation purchased by the mineralogist for the university library, the current University Library of Naples, deals with the sources used.The transcription of the unpublished archival documents preserved both in the archives of the Royal Mineralogical Museum of the University of Naples Federico II and in the State Archives of Naples constitutes the heart of the work; especially the numerous book catalogues can shed light on the relationships of the nineteenth-century academic world.Over the years, especially in recent decades, several studies have had the mineralogy museum as their object, but perhaps for the first time the emphasis is on the library.